Statistical analysis of management data - Gatignon, Hubert (New York: Springer, 2010)
Statistical Analysis of Management Data provides a comprehensive approach to multivariate statistical analyses that are important for researchers in all fields of management, including finance, production, accounting, marketing, strategy, technology, and human resources. This book is especially designed to provide doctoral students with a theoretical knowledge of the concepts underlying the most important multivariate techniques and an overview of actual applications. It offers a clear, succinct exposition of each technique with emphasis on when each technique is appropriate and how to use it. This third edition, fully revised, updated, and expanded, reflects the most current evolution in the methods for data analysis in management and the social sciences. In particular, this edition includes: a new chapter on the analysis of mediation and moderation effects, examples using STATA for most of the statistical methods, example of XLSTAT applications. Featuring numerous examples, the book may serve as an advanced text or as a resource for applied researchers in industry who want to understand the foundations of the methods particularly relevant and typically used in management research, and to learn how they can be applied using widely available statistical software.
Multivariate normal distribution -- Reliability alpha , principal component analysis, and exploratory factor analysis --Confirmatory factor analysis -- Multiple regression with single dependent variable -- System of equations -- Canonical correlation analysis -- Categorical dependent variables -- Rank-order data -- Error in variables: analysis of covariance structure- structural equation models -- testing mediation and moderation effects -- Cluster analysis -- Analysis of similarity and preference data -- Appendices
Includes bibliography and index
Keywords: Statistics -- Categorical Data Analysis; Statistics -- Management